E-Learning: Inovasi Media Pembelajaran di Era Digital - Wati, Erlina Eka; Husnia, Masna Binta Aida; Anbiya, Bakti Fatwa (LPPM Sekolah Tinggi Agama Islam Darul Falah, 2024)
This study aims to explain the concept of E-Learning in general as a learning medium in the digital era which includes: 1) definition; 2) characteristics and benefits; 3) advantages, disadvantages, constraints and effectiveness of application; 4) analysis and development design; 5) the function of the e-learning system; 6) development of